2023
DOI: 10.3390/foods12163069
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Use of Propolis in the Production of Dipping Sauce Powder as a Functional Food to Mitigate Testicular Toxicity Induced by Cadmium Chloride: Technological and Biological Evidence

Abstract: Propolis is a common natural ingredient used in food production, food packaging, and pharmaceutical products. Therefore, the aim of our study was to prepare dipping sauce powders as an innovative functional product with a regular and spicy taste from economical raw materials with high nutritional value. The developed products were fortified with propolis powder at 250, 500, and 750 mg/kg. All studied dipping sauces were subjected to a palatability test, a nutritional evaluation, and a microbiological assay per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In the south hemisphere, the values decrease to 127-142 mg GAE/g and 33-53 mg QE/g in Brazil [29]. Noteworthy, our values are also in the same range as the ones from Chinese (135.26 mg GAE/g and 29.03 mg QE/g) and Egyptian (200.70 mg GAE/g and 91.86 mg QE/g) propolis used in a recent study demonstrating their preventive potentialities in male reproductive function impairment [27]. The chemical composition of propolis is strongly dependent on the plant sources available around the hive, the geographical and climatic conditions, as well as the surrounding flora [30][31][32].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the south hemisphere, the values decrease to 127-142 mg GAE/g and 33-53 mg QE/g in Brazil [29]. Noteworthy, our values are also in the same range as the ones from Chinese (135.26 mg GAE/g and 29.03 mg QE/g) and Egyptian (200.70 mg GAE/g and 91.86 mg QE/g) propolis used in a recent study demonstrating their preventive potentialities in male reproductive function impairment [27]. The chemical composition of propolis is strongly dependent on the plant sources available around the hive, the geographical and climatic conditions, as well as the surrounding flora [30][31][32].…”
Section: Discussionsupporting
confidence: 78%
“…Administration of propolis in rats and rabbits shows an improvement in body and reproductive organs’ weight, an increase in sperm production, motility, count, and quality, and a reduction in abnormal and dead sperm numbers [ 19 , 22 , 23 , 24 , 25 ]. In co-administration with OS-inducers, like cadmium, aluminum, and copper, propolis ameliorated testicular histopathological and biochemical alterations, decreased the number of apoptotic cells, increased the levels of antioxidant enzymes, with a simultaneous decrease in malonaldehyde levels, a marker of lipid peroxidation [ 19 , 21 , 26 , 27 ]. In men, propolis administration was demonstrated to reduce the free radical-induced lipid peroxidation, as well as increase superoxide dismutase (SOD) activity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, propolis therapy enhances the weight of organs, body weight, semen characteristics, and testosterone hormone [ 9 ]. In addition, biological data demonstrated that all tested propolis-enriched dipping sauce samples improved all cadmium chloride-induced testicular histological and biochemical changes [ 10 ]. Doxorubicin (DOX) is a highly effective lipid-coated anticancer drug used in chemotherapy [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%